Construction of the national inventory of Chilean flora and fauna (Who is who in) the construction of the national inventory of vascular plants and vertebrates of Chile: historical patterns, productivity, and national contribution - Castro-Morales, S (SPRINGER, 2026)
Knowledge of Chile s biodiversity has long relied on taxonomists who formally describe species. Yet the principal contributors to this effort and their relative contributions to the national species inventory, remain poorly documented. This study addresses that gap with a historical, comparative analysis of taxonomic authorities responsible for describing native vascular plants and vertebrates in Chile, drawing on a comprehensive basionym database that records for each name, the authority, nationality (Chilean or foreign), and year of publication. A total of 1,121 authorities responsible for the description of 6,380 species was identified, with a clear predominance of foreign taxonomists (90.5%) over Chileans (9.5%). Overall, 75% of vascular plants and 91% of vertebrates have been described by foreign authorities. Most of these descriptions are attributable to a small number of highly productive and specialized taxonomists, whereas the majority of authorities contributed only a limited number of descriptions. The historical trajectories of species accumulation curves show marked differences between plants and vertebrates, with distinctive non-saturation patterns and description rates for each group. In recent decades, there has been a sustained increase in the participation of Chilean authorities and a positive rate of new species descriptions across most taxa. Overall, these results highlight the historically individualized and predominantly foreign nature of the species description process in Chile, which has led each taxon to develop its own largely independent trajectory. Strengthening training, funding, and collaboration within the discipline at the national level is essential to address the remaining challenges in the knowledge of Chilean biodiversity.